Storynomics Tourism: Promosi Daya Tarik Wisata di Kawasan Wae Bobok Kabupaten Menggarai Barat Melalui Tradisi Lisan - Ni Nyoman Arini; I Nengah Sandi Artha Putra; Ida Ayu Karina Putri (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2024)
This study aims to analyze oral traditions that have potential as tourist attractions in the Wae Bobok Area. Local communities can use this cultural heritage to promote storynomics tourism in Wae Bobok Area while preserving it. The approach used in this study is qualitative to explore various aspects of folklore relevant to tourism, such as cultural values, local cultural heritage, and tourist attractions. The type of data used in this study is qualitative data. Data was collected through observation, interviews, and documentation. The results of this study show that the oral tradition that developed in Wae Bobok has great potential as a promotional medium to introduce the charm of natural tourism such as springs, Cunca Pengantin, and beautiful scenery from “Jurang Maut”. In addition, there is also potential to promote cultural tourism wealth which includes traditional Tuak Reis and Manuk Kapu rituals, as well as local gastronomy such as rebok. Oral traditions such as folklore, myths, and traditional rituals can be an important part of enriching the tourist experience, while preserving the local cultural heritage. Through proper promotion, oral traditions can become a unique tourist attraction and certainly distinguish Wae Bobok from other tourism destinations, as well as help build awareness of the importance of cultural preservation.